2021
DOI: 10.1126/sciadv.abf9395
|View full text |Cite
|
Sign up to set email alerts
|

Skillful prediction of summer rainfall in the Tibetan Plateau on multiyear time scales

Abstract: Skillful near-term climate predictions of rainfall over the Tibetan Plateau (TP), the Asian water tower, benefit billions of people. On the basis of the state-of-the-art decadal prediction models, we showed evidence that although the raw model outputs show low predicted ability for the summer Inner TP (ITP) rainfall due to low signal-to-noise ratios in models, we can produce realistic predictions by extracting the predictable signal from large ensemble predictions along with a postprocessing procedure of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Compared to the other two main wetland regions of China, an expansion of potential habitats for wetland species in the Tibetan Plateau is distinct under climate change, according to our predictions, especially toward northern colder and drier areas, which is in accordance with our expectation, since a warmer and wetter climate in this region has been predicted by future climate models (Fu et al., 2021; Hu & Zhou, 2021). Besides, wetland species would also benefit from more water supply brought by concomitant glacial melting and permafrost thawing, though over the short term (Chao et al., 2020; Gao et al., 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Compared to the other two main wetland regions of China, an expansion of potential habitats for wetland species in the Tibetan Plateau is distinct under climate change, according to our predictions, especially toward northern colder and drier areas, which is in accordance with our expectation, since a warmer and wetter climate in this region has been predicted by future climate models (Fu et al., 2021; Hu & Zhou, 2021). Besides, wetland species would also benefit from more water supply brought by concomitant glacial melting and permafrost thawing, though over the short term (Chao et al., 2020; Gao et al., 2021).…”
Section: Discussionsupporting
confidence: 91%
“…This has been termed the "signal-tonoise paradox" (SNP, Scaife and Smith, 2018) since a model can unexpectedly predict the real world better than itself despite being a perfect representation of itself. First diagnosed in seasonal forecasts of the NAO (Eade et al, 2014;Scaife et al, 2014) the SNP has now been found in sub-seasonal (Domeisen et al, 2020), seasonal (Baker et al, 2018;Dunstone et al, 2018), interannual (Dunstone et al, 2016(Dunstone et al, , 2020, multi-annual (Sheen et al, 2017;Yeager et al, 2018;Hu and Zhou, 2021) and decadal (Smith et al, 2019aAthanasiadis et al, 2020) forecasts. On seasonal timescales the SNP occurs mainly in the extratropics, especially the North Atlantic where the NAO signal is underestimated by a factor of 2 to 3 (Eade et al, 2014;Scaife et al, 2014;Dunstone et al, 2016;Baker et al, 2018).…”
Section: Lesfmip Experiments and Analysismentioning
confidence: 99%
“…Decadal climate predictions are now issued operationally by the World Meteorological Organisation (WMO) and offer the potential to provide early warnings of changes in climate (Kushnir et al, 2019). By comparing retrospective forecasts (hindcasts) with observations, it has been established that decadal predictions can potentially forecast many aspects of climate over the coming years, including Atlantic Multidecadal Variability (AMV, Doblas-Reyes et al, 2013;Hermanson et al, 2014;Yeager and Robson, 2017;Borchert et al, 2021), Atlantic hurricane activity (Smith et al, 2010;Caron et al, 2018), Sahel rainfall (Sheen et al, 2017;Yeager et al, 2018), droughts and wildfires in southwestern United States (Chikamoto et al, 2017), carbon fluxes (Li et al, 2019;Lovenduski et al, 2019a,b), European precipitation and temperature in summer (Müller et al, 2012;Yeager et al, 2018) and winter (Simpson et al, 2019), summer temperatures in north-east Asia (Monerie et al, 2018), the occurrence of warm summer temperature extremes (Borchert et al, 2019), Tibetan Plateau summer rainfall (Hu and Zhou, 2021), and winter atmospheric circulation in the North Atlantic (Athanasiadis et al, 2020;. Each year the WMO issues a Global Annual to Decadal Climate Update (GADCU, Hermanson et al, 2022) that synthesizes the forecasts from several international centers.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, TP snow cover plays a more important role in the TP snow/ice‐related hydrological effect than glacier cover. Therefore, investigating the influence of TP snow/glaciers on water budgets is imperative for climatic early warning, water resource utilization and species security (Hu & Zhou, 2021; Kang et al., 2010; Xu et al., 2008; You et al., 2021). However, compared to TP glaciers, TP snow‐related hydrological effects are not well understood.…”
Section: Introductionmentioning
confidence: 99%